2020
DOI: 10.1186/s13195-020-00617-2
|View full text |Cite
|
Sign up to set email alerts
|

A selective p38α/β MAPK inhibitor alleviates neuropathology and cognitive impairment, and modulates microglia function in 5XFAD mouse

Abstract: Background: Chronic neuroinflammation, aggressive amyloid beta (Aβ) deposition, neuronal cell loss, and cognitive impairment are pathological presentations of Alzheimer's disease (AD). Therefore, resolution of neuroinflammation and inhibition of Aβ-driven pathology have been suggested to be important strategies for AD therapy. Previous efforts to prevent AD progression have identified p38 mitogen-activated protein kinases (MAPKs) as a promising target for AD therapy. Recent studies showed pharmacological inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 59 publications
3
49
1
Order By: Relevance
“…Specifically, the compound MW150 was active in APP-transgenic and tau-transgenic mice [121,123], the compounds MW181 and SB2399063 in aged tauopathy mice [122], and neflamapimod/VX-745 in aged rats [120]. In addition, a very recent publication demonstrated that oral administration of a selective p38 α/β inhibitor, NJK14047, to 9-month old 5XFAD (APP) transgenic mice reduced levels of amyloid-beta deposits, reduced spatial memory loss and reduced the number of degenerating neurons labeled with Fluoro-Jade B [41]. Moreover, genetic reduction of neuronal p38α in APP overexpressing transgenic mice improved synaptic transmission, decreased memory loss and reduced amyloid pathology [124,125].…”
Section: Therapeutic Potential In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the compound MW150 was active in APP-transgenic and tau-transgenic mice [121,123], the compounds MW181 and SB2399063 in aged tauopathy mice [122], and neflamapimod/VX-745 in aged rats [120]. In addition, a very recent publication demonstrated that oral administration of a selective p38 α/β inhibitor, NJK14047, to 9-month old 5XFAD (APP) transgenic mice reduced levels of amyloid-beta deposits, reduced spatial memory loss and reduced the number of degenerating neurons labeled with Fluoro-Jade B [41]. Moreover, genetic reduction of neuronal p38α in APP overexpressing transgenic mice improved synaptic transmission, decreased memory loss and reduced amyloid pathology [124,125].…”
Section: Therapeutic Potential In Admentioning
confidence: 99%
“…During the last two decades, deregulated p38α has emerged as a leading therapeutic target for AD and has also been associated with the pathology of other neurodegenerative disorders, including PD, DLB, or ALS [ 4 , 19 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. These therapeutic opportunities for treatment with selective, brain-penetrant p38α inhibitors will be discussed in more details in Section 6 .…”
Section: Overview Of the P38α Isoform As A Member Of The P38 Mapk mentioning
confidence: 99%
“…In response to Aβ, NTF, or oxidative stress, also a common feature in AD brains, JNK and p38 induce NF-kβ, synaptic excitotoxicity, and neuroinflammation [ 123 , 124 , 125 , 126 , 127 ]. Corroborating these findings, it was demonstrated that NJK14047 (selective p38α/β inhibitor) reduced NOS, COX-2, TNF-α, and IL-1β in vitro, decreased microglia activation in vivo [ 128 ], and improved cognitive functions in an AD mouse model [ 129 ]. This could be explained by the fact that p38α expression stimulates BACE1 and, therefore, the Aβ generation, but also induces dysfunctional autophagy in neurons [ 129 ].…”
Section: General Aspects Of Mitogen-activated Protein Kinases (Mapmentioning
confidence: 99%
“…Entry points, which were systematically used throughout the experiment, were in other three quadrants and spaced equally around the edge of the tank. Briefly, the animals were trained for 90 seconds repeatedly to find the platform using visual information around and time taken (escape latency) to find the hidden platform was recorded as the learning (acquisition) process [37]. Mice who can not find the platform within 90 seconds were guided to the platform and the escape latency of it was recorded as 90 seconds.…”
Section: Morris Water Maze Test (Mwm)mentioning
confidence: 99%